PERADILAN ADAT DAYAK KANAYATN OLEH DEWAN ADAT TERHADAP PELAKU PENARIKAN BENDA PUSAKA DI RUMAH RADAKNG KOTA PONTIANAK - ANDRIANUS NIM. A1011161032 (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractThe Kanayatn Dayak community, until now, are still bound by the provisions of customary law which are used as instruments to control social life and local natural resources. Anyone who violates the provisions of customary law will face customary courts. Every conflict, dispute or dispute among the Dayak Kanayatn indigenous peoples is resolved through customary court decisions decided by traditional leaders in accordance with the provisions of the customary law of the Kanayatn Dayak community. Deliberation is like a spirit or soul for dispute resolution through customary law. It is not surprising that the settlement of cases through customary courts led by the Temenggung rarely leads to lawsuits in state courts. Both the victim and the defendant are satisfied. Decisions are made through deliberation by prioritizing harmony, propriety, and harmony.The formulation of the problem in this study is